2020
DOI: 10.1177/0146167220935737
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Moralized Attitudes Over Time

Abstract: When people perceive a moral basis for an attitude, that attitude tends to remain durable when directly challenged. But are moral concerns only influential in the moment or does moralization also signal an attitude that endures over time? Five longitudinal studies considering attitudes toward 19 different topics tested whether attitudes are more stable over time when people report that they are more morally based. Across studies, we find support for the hypothesis that degree of attitude moralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…It is measured by meta-judgmental measures and usually, but not always, measured in relation to the attitude/evaluation (e.g., Skitka, 2014 ) rather than the object (e.g., Conner et al, 2022b ). Various studies have shown such attitudes to be more stable ( Luttrell and Togans, 2021 ) and to better predict behavior ( Skitka and Bauman, 2008 ; Judge et al, 2012 ). For example, Conner et al (2022b) showed a measure of moral conviction taken in relation to the object (e.g., “Morally, wearing a face covering in public places is the right thing to do?…”
Section: Predictors Of Strengthmentioning
confidence: 99%
“…It is measured by meta-judgmental measures and usually, but not always, measured in relation to the attitude/evaluation (e.g., Skitka, 2014 ) rather than the object (e.g., Conner et al, 2022b ). Various studies have shown such attitudes to be more stable ( Luttrell and Togans, 2021 ) and to better predict behavior ( Skitka and Bauman, 2008 ; Judge et al, 2012 ). For example, Conner et al (2022b) showed a measure of moral conviction taken in relation to the object (e.g., “Morally, wearing a face covering in public places is the right thing to do?…”
Section: Predictors Of Strengthmentioning
confidence: 99%
“…Increasing attitude cer-tainty, attitude importance, attitude subjective knowledge, and moral basis of attitude and decreasing felt ambivalence, potential ambivalence and inconsistency were individually associated with attitudes being more stable. Similar individual effects on attitude stability have been reported for attitude certainty (Bassili, 1996), attitude importance (Krosnick, 1988), attitude subjective knowledge (Bartle, 2000), moral basis of attitude (Luttrell & Togans, 2021), and felt ambivalence (Conner & Armitage, 2008). There have been fewer tests of the individual effects of potential ambivalence (Conner & Armitage, 2008), potential cognitive-affective ambivalence and inconsistency in particular (Conner et al, 2021) on attitude stability.…”
Section: Summary Of the Main Findingsmentioning
confidence: 99%
“…In Study 4, we wanted to extend the prior findings, examining whether attitude moralization also predicts people's reports of their actual purchasing behaviors at some point in the future. Although there is some evidence that perceived moral bases for political attitudes are associated with reports of one's actual behavior (Skitka & Bauman, 2008) and that more moralized attitudes tend to be more stable over time (Luttrell & Togans, 2021), we are not aware of any prior evidence directly showing that attitude moralization prospectively predicts behavioral reports at some point in the future. Thus, we employed a longitudinal design in which we used people's reported degree of moral basis for their attitudes toward organic food at Time 1 to predict reports of whether they had purchased organic food two months later.…”
Section: Studymentioning
confidence: 77%
“…although moralization tends to correspond with certainty and ambivalence, its effects are empirically unique from these other constructs Luttrell & Togans, 2021;Philipp-Muller, Wallace, & Wegener, 2020;Skitka, Bauman, & Sargis, 2005). Therefore, to show that moralization predicts additional variance in purchase intentions beyond these other impactful attributes, we measure and control for them in all analyses.…”
Section: Studymentioning
confidence: 99%